Turning on learning : five approaches for multicultural teaching plans for race, class, gender, and disability - Grant, Carl A.; Sleeter, Christine E., 1948- (Upper Saddle River, N.J. : Merrill, 1998)
Teaching the exceptional and culturally different. Human relations. Single-group studies. Multicultural education. Education that is multicultural and social reconstructionist.
Keywords: Education; Curricula; United States; Multicultural education -- United States -- Curricula -- Handbooks, manuals, etc; Teaching -- Aids and devices -- Handbooks, manuals, etc